2017
DOI: 10.1007/s11071-017-3791-8
|View full text |Cite
|
Sign up to set email alerts
|

A coupled-field model of a rotating composite beam with an integrated nonlinear piezoelectric active element

Abstract: The dynamics of a system consisting of a rotating rigid hub and a thin-walled composite beam with embedded active element is presented. The beam comprises of a generally orthotropic host made of an arbitrary laminate and an additional layer of a transversely isotropic piezoceramic material. The higherorder constitutive relations for piezoelectric are used to properly model its electromechanical structural behaviour when operated in near resonance conditions or subjected to strong electric fields. In the mathem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Detailed derivation procedure of a six-DOF model of the beam with an arbitrary presetting angle θ and any circumferential lamination scheme has been presented in former authors papers [17] and [18]. These papers include also the list of adopted kinematic and structural assumptions to the mathematical model as well as the discussion on their significance.…”
Section: Piezoelectric Materials Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed derivation procedure of a six-DOF model of the beam with an arbitrary presetting angle θ and any circumferential lamination scheme has been presented in former authors papers [17] and [18]. These papers include also the list of adopted kinematic and structural assumptions to the mathematical model as well as the discussion on their significance.…”
Section: Piezoelectric Materials Modelmentioning
confidence: 99%
“…It has been shown the electromechanical coupling in the structure comes from the shear deformation in flapwise bending plane. This model has been adopted in later research for the analysis of a rotating thin-walled composite beam with embedded piezoelectric layer [17]. In studies, a specific case of circumferentially asymmetric stiffness lamination scheme that exhibits flapwise bending and twist mode elastic coupling was considered.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the piezoelectric coefficients reported here are specific to the Navy type II PZT used in the MFC, and do not represent the total piezoelectric coefficients of the MFC itself. Two models are tested here in ABAQUS: a specialized method which accounts for the MFC's modular structure [22], and a thermal analogy [23].…”
Section: Numerically Solving For Deformed Geometrymentioning
confidence: 99%
“…They showed that the proposed model not only provided good numerical precision and efficiency, but also overcome the constraints expressed by Cartesian variables of a previous traditional nonlinear model. The dynamics of a structure consisting of a rotating rigid hub and a thin-walled composite beam with an embedded active part were introduced by Latalski [7].…”
Section: Introductionmentioning
confidence: 99%